Serum HOTAIR and GAS5 levels as predictors of survival in patients with glioblastoma. Issue 1 (10th October 2017) - Shen, Jie; Hodges, Tiffany R.; Song, Renduo; Gong, Ye; Calin, George A.; Heimberger, Amy B.; Zhao, Hua
Abstract : Circulating long non‐coding RNAs (lncRNAs) are a new class of cancer biomarkers. However, their significance in predicting outcomes in glioblastoma patients is unclear. We measured the levels of six known oncogenic lncRNAs—CRNDE, GAS5, H19, HOTAIR, MALAT1, and TUG1 in serum samples from 106 patients with primary glioblastoma and analyzed their association with outcomes. High levels of HOTAIR were associated with decreased probability of 2‐year overall survival (adjusted hazard ratio [HR] = 2.04; 95% confidence interval [CI] = 1.08‐9.76), and disease‐free survival (adjusted HR = 1.82; 95% CI = 1.04‐6.17). High levels of GAS5 were associated with increased probability of 2‐year overall survival (adjusted HR = 0.44; 95% CI = 0.18‐0.99), and disease‐free survival (adjusted HR = 0.46; 95% CI = 0.16‐0.98). HOTAIR and GAS5 levels could serve as reciprocal prognostic predictors of survival and disease progression in patients with glioblastoma.